INTEGRATED SURFACE-SUBSURFACE MODEL FOR IN-PLACE UNCERTAINTY STUDY IN GAMMA FIELD GAS CAP BLOWDOWN SCENARIO - Adhika Jala Putra, Devara
Gamma Field is located in Block B of South Natuna Sea consisting of five separated reservoirs in three geological zones. Upper and Lower reservoirs are mature reservoir and are being produced since 2008 with gas lift and gas injection production scenario for Lower reservoir. Both become the main focus in this study. Upper and Lower reservoir are gas cap with an oil rim reservoir. Upper reservoir has been showing a declining oil production rate last few years and is planned to employ gas blow-down scenario in order to maximize gas sales. Ineffective gas injection scenario on Lower reservoir resulting in gas recycling leads toward gas cap blow-down development scenario to increase gas sales volumes. This problem also creates uncertainty in hydrocarbon in-place volume estimation. Besides, better estimation about in-place volume could improve field development study. This study focuses on capturing gas cap blow-down scenario potential on Upper and Lower reservoir during remaining years by varying oil and gas in-place volume. Integrated surface-subsurface model is built using commercial software by Petroleum Experts as a tool to conduct comprehensive analysis from reservoir modelling to production forecasting. The study shows that the bigger the gas cap size, the more energy support for reservoir, thus production rate could be maintained over study period. Lowering 41% gas in-place input for Upper reservoir exhibits more significant impact to its production performance that lowering 44% on Lower reservoir. Evidently, there is a trend of decreasing contractor NPV as the value of gas in-place is reduced during economic evaluation.